The Role of Self-Regulated Learning and Gender in Determining Student Academic Achievement: A Comparative Analysis - Sandayanti, Vira; Supriyati, Supriyati (Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractAcademic achievement is the level of success in studying the learning material. It can be seen from the GPA, which is a number that describes the success of studies cumulatively (Saputro, 2022). Academic achievement factors (Arofah et al., 2020) include internal factors (physiology and psychology) and external factors (social and non-social environment). The study aimed to determine the differences in student academic achievement in terms of Self-Regulated Learning (SRL) and gender. The research sample was 160 students of the Faculty of General Medicine class of 2022 at Malahayati University, determined by random sampling technique. The data was collected using the MSLQ (Motivated Strategies for Learning Questionnaire) scale, 2021/2022 academic year GPA, and students’ gender. The correlation test results were 0.562 (p = 0.000), where the p-value was lower than 0.05. Therefore, the proposed research hypothesis proved differences in academic achievement in terms of SRL and gender in the Faculty of General Medicine students at Malahayati University. The SRL contributed to academic achievement by 32%.